2019
DOI: 10.1158/1535-7163.mct-18-0770
|View full text |Cite
|
Sign up to set email alerts
|

GnRH-R–Targeted Lytic Peptide SensitizesBRCAWild-type Ovarian Cancer to PARP Inhibition

Abstract: EP-100 is a synthetic lytic peptide that specifically targets the gonadotropin-releasing hormone receptor on cancer cells. To extend the utility of EP-100, we aimed to identify effective combination therapies with EP-100 for ovarian cancer and explore potential mechanisms of this combination. A series of in vitro (MTT assay, immunoblot analysis, reverse-phase protein array, comet assay, and immunofluorescence staining) and in vivo experiments were carried out to determine the biological effects of EP-100 alone… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 58 publications
(60 reference statements)
1
4
0
Order By: Relevance
“…In this study, we found that the combination of olaparib and ONC206 showed significant effects on the AKT/mTOR/S6 pathway compared to ONC206 or olaparib alone. The finding of increased inhibition of the PI3K/AKT/mTOR pathway with the combination therapy is consistent with prior studies evaluating this treatment strategy 15 , 45 , 51 , 57 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, we found that the combination of olaparib and ONC206 showed significant effects on the AKT/mTOR/S6 pathway compared to ONC206 or olaparib alone. The finding of increased inhibition of the PI3K/AKT/mTOR pathway with the combination therapy is consistent with prior studies evaluating this treatment strategy 15 , 45 , 51 , 57 .…”
Section: Discussionsupporting
confidence: 88%
“…This pathway exerts a profound impact on downregulation of BRCA1 and BRCA2, the process of DNA damage repair, and the maintenance of genome stability. Activation of the PI3K/AKT pathway is associated with acquired resistance to PARP inhibitor treatment and may compromise the efficacy of PARP inhibitors 19 , 51 , 52 . PTEN-deficient tumors present an enhanced sensitivity to the combination of PI3K and PARP inhibition in EC cells and in a PTEN-deficient mouse model of EC 19 , 53 .…”
Section: Discussionmentioning
confidence: 99%
“…EP-100 a fusion peptide in which 18-amino-acid cationic α-helical lytic peptide (CLIP-71) is covalently linked to GnRH, was created to deliver lytic peptides to GnRH receptor-positive cancer cells [ 155 ] ( Table 2 ). It was recently shown, that EP-100 in combination with PARP inhibitor olaparib is a promising strategy for the therapy of ovarian cancer [ 156 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have indicated that KNG1 is highly related to the gonadotropin-releasing hormone (GnRH) ( 22 ), which is a hypothalamic neuropeptide that plays an important role in the reproductive system. Investigators have made a great effort to develop GnRH agonists and antagonists for the treatment of tumors such as ovarian cancers ( 23 ). Coagulation factor II (F2) is found to be overexpressed in various epithelial neoplasms including ovarian cancer ( 24 ); F2 receptor, also known as PAR1, has been provided to be differentially expressed in ovarian cancer tissue ( 25 ).…”
Section: Case Studymentioning
confidence: 99%